The State: Individual Freedom and the Complexities of JusticeA Reading of Robert Nozick's Political Philosophy - Asst. prof. Dr. Alaa Kadhim Masood (Journal of College of Education, 2025)
The global community, particularly individuals, is experiencing injustice, oppression, and poverty. Political philosophers advocate defending and protecting individual rights. Therefore, the existence of the state is the primary reason for achieving justice despite the conflict and competition among individuals, which has created class disparities and a large gap between the rich and the poor. One of the most important issues in this confrontation is how to strike a balance between equality and freedom; how to preserve individual rights that are being violated by tax evasion and fees imposed by the state. Therefore, American political philosophy has worked to address the rights and freedoms of individuals in light of the implementation of the concept of justice. Although John Rawls is the most prominent philosopher through his writings on justice, we find Robert Nozick matching him and differing with him in the lack of sympathy based on the application of justice, as in his book (Anarchy, State, Utopia), as he worked to apply equality among individuals not only in the distribution of wealth, but equality even in the fortunes and equal opportunities for individuals without disparity between them on the basis of class balances or political differences, as everyone shares the same rights as well as the sharing of duties.‎
Keywords: Justice, State, Anarchy, Utility, Robert Nozick.